Administrative procedures as guarantee of acess to justice in tax procesures (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The administrative process for being originary of the act practiced by the Administration, allows the ingress as much in the juducial way as in the administrative. However, in the booth cases there is na extremely time consuming process, wich dificults the taxpayer to have a quick and effective answer from the Administration as to the tax problem suffered by him. Thus, the presente article have by object the study of the administrative precedentes and its aplication in the administrative tax process, ensuring it greater speed and predictability, enabling the acces to justice, like the acces to a fair legal order (Kazuo Watanabe) to the tax payer. For that, will be utilized the hipotetic dedutive method in the elaboration, since it treats of proposed solutions, consisting in a conjecture. The methodologic procedure utilized was the bibliografic revision, jurisprudential and doctrinal analysis.